Effects of total dissolved gas supersaturation and sediment on environmental DNA persistence of grass carp (Ctenopharyngodon idella) in water - Huang, Lei; Zhang, Jianmin; Wang, Yurong (Frontiers in Environmental Science, 2022)
Environmental DNA (eDNA) technology has become an alternative tool for monitoring aquatic communities due to its sensitive, economical, and non-invasive properties. However, the application of this technique is often limited by the complexity of environmental conditions, which often poses a barrier to the transmission of biological information. Here, we conducted a series of experiments with grass carp as the target species to evaluate the effects of total dissolved gas (TDG) supersaturation and sediment on the persistence of eDNA in water. The results showed TDG supersaturation promoted eDNA decay in still water but with no significant effect in flowing water for rapid dissipation of TDG. For sediment, its presence accelerated the decay of eDNA no matter the flow conditions. The grass carp eDNA showed an exponential decay pattern in water and the decay rate constant decreased gradually with time. Our study highlights the importance of integrating experimental results with the natural environment and provides an important reference for species monitoring using eDNA technology in aquatic ecosystems with high dams built.